Denotative and Connotative Meaning in Arabic Texts: Implications for Enhancing Semantic Competence in Arabic Language Education - Fauzi, Ahmad; Susiawati, Iis (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study examines denotative and connotative meaning in Arabic texts and explores their contribution to strengthening the semantic competence of students in Arabic Language Education. Employing a qualitative literature review with a descriptive-analytical approach, the study analyzes scholarly works on Arabic semantics, contextual meaning construction, and pedagogical strategies in language instruction. The findings indicate that denotative meaning provides lexical clarity and structural accuracy in understanding Arabic texts, while connotative meaning enhances interpretative depth by integrating cultural, contextual, and pragmatic dimensions. The interaction between these two layers of meaning plays a crucial role in developing students’ semantic sensitivity, interpretative skills, and critical linguistic awareness. Furthermore, the study highlights that the systematic integration of denotative and connotative analysis within instructional design—supported by contextual learning strategies and digital resources—can significantly improve students’ semantic competence. These findings suggest that semantic instruction in Arabic language education should move beyond literal interpretation toward contextualized and meaning-oriented approaches that foster deeper comprehension and communicative proficiency.